The Christology of John Duns Scotus - Jared Isaac Goff (Religions, 2025)
The subtle Christology of John Duns Scotus has been the focus of intense study and dispute since his death in 1308. Of note are the Scottish theologian’s positions on the predestination of the Incarnation, his definition and metaphysical account of personhood, and his understanding of the status of the existence of Christ’s human nature. Each of these has bearings on his understanding of grace and atonement. This essay provides an introductory and summary overview of Scotus’s characteristic positions on the Incarnation and redemption in the light of his theological context and influences, arguing for the coherency and importance of his distinctive Christology.